Space Efficiency of Transit-Oriented Station Areas: A Case Study from a Complex Adaptive System Perspective - Jinwen Fan; Zhenwu Shi; Jie Liu; Jinru Wang (ISPRS International Journal of Geo-Information, 2025)
Transit-oriented development (TOD) has been widely adopted in urban planning to alleviate traffic congestion, urban sprawl, and other problems. The TOD metro station area, as a dynamic and open spatial system, presents typical complex features. To improve urban planning by understanding the complex features of metro station areas, this study proposes a comprehensive evaluation method using complex adaptive system theory (CAS) to assess space efficiency and the use of an evaluation method like COWA (continuous ordered weighted averaging) operator and cloud model to show efficiency. Factors include external relevance, internal coordination, and environmental adaptation. This study uses Museum Station of Harbin Railway Transportation as the case study, and the results show that the space efficiency of Harbin’s TOD metro station areas are lacking in internal coordination and environmental adaptation. The proposed evaluation method not only identifies areas of space inefficiencies in urban rail transit station areas but also provides valuable insights for informed decision-making and future urban development initiatives.